THE IMPLEMENTATION OF ANIMAL WELFARE ASPECTS TO DOG CARE IN BANJAR BATUSARI, SANGEH VILLAGE, ABIANSEMAL DISTRICT, BADUNG REGENCY, BALI - Dharma, I Gusti Made Alit Surya; Sukada, I Made; Mufa, Romy Muhammad Dary (Buletin Veteriner Udayana; Vol. 15 No. 6 December 2023, 2023)
Animal welfare is a form of animal rights to fulfill the physical, psychological needs of animals and environmental conditions that are suitable for these animals. The concept of animal welfare is known as the five freedoms, this provision requires that all animals kept have the following rights/freedoms, namely: freedom from hunger and thirst, freedom from heat and discomfort, freedom from injury, disease and pain, freedom from fear and suffering, and freely express natural behavior. This study aims to describe the application of animal welfare to dog rearing in Banjar Batusari, Sangeh Village, Abiansemal District, Badung Regency, Bali. Data collection was carried out by means of census interviews with all the heads of families (KK) of dog owners in Batusari Banjar, Sangeh Village, Abiansemal District, Badung Regency, Bali. The data obtained from the interviews will be tabulated using Ms.word and IBM SPSS and then the percentage of the amount of data that is in accordance with animal welfare practices and the percentage of the number of data that deviate is calculated. The results show that the application of the principle of freedom from discomfort is 46.9%, the application of the principle of freedom from hunger and thirst is 55.6%, the application of the principle of freedom to express natural behavior is 51.6%, the application of the principle of freedom from fear and stress is 97.6%, and the Finally, the application of the principle of being free from pain, injury and disease is 29.2%. Overall, the principles of animal welfare have been implemented by dog-owning households in Banjar Batusari, Sangeh Village, Abiansemal District, Badung Regency, Bali, although there is still a need to increase the application of some of the principles.